Bank Interest Rates for Micro and Small Companies (MYPE’S), Peru, 2015 – 2018 - Rosales Dominguez, Ediht Geobana (2020)
The objective of this article was to analyze the Bank interest rates for Micro and Small Businesses (Mypes), Peru, 2015 to 2018, being of great importance the research since Mypes are 99.4% of companies in the country and provide 88 % of employment. The type of investigation was descriptive, analytical - deductive and comparative - historical method. The results indicated that the Bank’s active interest rates were for micro-enterprises: 34.89% (2015), 37.19% (2016), 36.29% (2017) and 32.70% (2018) and for small companies: 20.45% (2015), 21.65% (2016), 19.76% (2017) and 18.50% (2018); both in national currency. Concluding, that between the years 2015 to 2018, the banks determined high active interest rates, as a result of the freedom granted by Article 9 of the Banking Law, and the behavior they presented was the product of the monetary policy established by the BCRP, since the interest rates varied depending on them.